The Incident Management Measurement Tool (IMMT): A Tool for Measuring Public Health Incident Management During and After Emergencies - Parks, Vanessa; Clark-Ginsberg, Aaron; Awan, Jalal; Balagna, Jay; Hindmarch, Grace; Fraade-Blanar, Laura; Fisher, Holly; Vagi, Sara; Renard, Paul; Nelson, Christopher D. (Disaster medicine and public health preparedness, 2025)
Risks and priorities change during the management of public health incidents. Here we describe a new tool, the Incident Management Measurement Tool (IMMT), that can be used to inform midcourse corrections during public health emergencies and realistic exercises. We developed the IMMT through a literature review and subject matter expert interviews. We field tested the tool in 23 incidents ranging in size, duration, and complexity, making changes based on user feedback. The IMMT consists of 2 modular data collection methods, a survey of the incident management team and a protocol for a peer assessor. Pilot testing suggested that the tool is valid, reliable, feasible, and useful. Measurement of public health incident management is feasible and may be useful for improving response times and outcomes. Moreover, a limited set of standard measures is relevant to a wide range of incident response contexts.